A New Consensus Protocol: Quadratic Voting With Multiple Alternatives - Eguia, Jon X.; Immorlica, Nicole; Ligett, Katrina; Weyl, E. Glen; Xefteris, Dimitrios (2019)
We study a voting scheme for multiple alternatives. Our scheme generalizes the two-alternative quadratic voting scheme of Lalley and Weyl. We prove that our generalization results in an outcome where the most-valued alternative wins, and that the vote totals order alternatives from most-to-least valued.